Will they or won't they : a novel - Wilder, Ava (Dell, 2023)
"On screen, they're in love. Off screen, they can't stand each other. Two co-stars with a complex history reunite to film the final season of a beloved paranormal drama in this tension-filled will they won't they romance from the author of How to Fake It in Hollywood. Lilah Hunter and Shane McCarthy are madly in love-well, their characters are in love on the hit paranormal TV show Intangible. It's been years since Lilah and Shane have actually enjoyed each other's company, especially since Lilah ditched the cast at the end of season five in hopes of becoming a film star. With no such luck, she's back to film the much-hyped ninth and final season. But coming back means facing one of the biggest reasons she left... Shane. Their intense romance was strictly behind the scenes during the first season of Intangible, until their fling imploded and started the bad blood between them. Now back on set together for the first time in years, and with the world's eyes on them and their post-show careers on the line, they'll have to grit their teeth and play nice. But with pressure from the studio to keep fans of their love story happy, the show runners make sure that Lilah and Shane's characters can't keep their hands (or lips) off each other. And if they're not careful, they just might get blindsided by one final twist: winding up together after the cameras stop rolling"--